2010
DOI: 10.1103/physrevb.81.224204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of the ordering of carbon in highly supersaturatedα-Fe

Abstract: A recently developed Fe-C interatomic potential has been used to investigate carbon in highly supersaturated ␣ iron with an emphasis on the possible ways in which carbon can arrange itself on the octahedral sites of the tetragonally distorted ␣-iron lattice. Focusing particularly on the composition Fe 16 C 2 , the embedded atom method potential used gives the same ground-state structure of Fe 16 C 2 as density-functional-theory calculations. Moreover, when computing C-C interactions between two carbon atoms at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 24 publications
7
38
0
1
Order By: Relevance
“…At higher temperatures, the high degree of ordering is lost, but the carbon still remains in only one of the three types of octahedral sites up to the eutectoid temperature. Both of these distributions of carbon result in high tetragonality, similar to what would be predicted based on the extrapolated behaviour observed in ferrous martensites [34]. It is only at very high temperatures that complete loss of tetragonality is expected in samples having high carbon contents.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…At higher temperatures, the high degree of ordering is lost, but the carbon still remains in only one of the three types of octahedral sites up to the eutectoid temperature. Both of these distributions of carbon result in high tetragonality, similar to what would be predicted based on the extrapolated behaviour observed in ferrous martensites [34]. It is only at very high temperatures that complete loss of tetragonality is expected in samples having high carbon contents.…”
Section: Discussionsupporting
confidence: 65%
“…Such an observation is consistent with previous reports of carbon superaturation (as detailed in ''Introduction'') including the general view that high levels of carbon in solid solution can be obtained in ferrite having a much lower tetragonality than what would be expected based on the extrapolated behaviour of ferrous martensites. In our recent study, using atomistic simulations [34], it was shown that within highly supersaturated ferrite (containing up to 12 at% C) carbon is favourably accommodated at low temperatures (below *800 K) and no applied stress, by being organized into a highly ordered structure where carbon resides on only one of three octahedral sites, commensurate with the Fe 16 N 2 phase observed in the Fe-N system. At higher temperatures, the high degree of ordering is lost, but the carbon still remains in only one of the three types of octahedral sites up to the eutectoid temperature.…”
Section: Discussionmentioning
confidence: 77%
“…Naraghi et al [9] corroborated in ThermoCalc that indeed the lowest free energy is obtained if spinodal decomposition is considered. Similar conclusions were presented by Sinclair et al [10] by means of molecular dynamics simulations. The ordered product of spinodal decomposition that corresponds to the carbon-rich part of the modulation is generally described as a superlattice structure that in literature is referred to as α -Fe 16 C 2 , illustrated in Figure 1(d).…”
Section: Introductionsupporting
confidence: 78%
“…The simulations such as those in [9,10,16,17] give an account for a specific phenomenon, either spinodal decomposition or carbon segregation to defects. However, the actual interaction between the two processes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, as more and more carbon atoms arrive to a volume in the vicinity of the dislocation, carbon-carbon interactions (in general repulsive at short separations, see Refs. [20,22]) play a role as important as carbon-dislocation interactions. This leads to the saturation of that volume, which is not able to accommodate any extra carbon atom.…”
mentioning
confidence: 99%